Pengaruh Budaya Sekolah, Kompetensi Profesional dan Komitmen Organisasi Terhadap Kinerja Guru SMP Negeri Air Putih Kabupaten Batu Bara - Hendra Robertho Siregar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine school culture, professional competence, and organizational commitment to teacher performance at SMP N Air Putih, Batu Bara Regency. This type of research is quantitative, where this research was conducted in all Air Putih Middle School schools in Batu Bara district. The population in this study was 98 people, so the sample used was 98 people. This research uses quantitative techniques. The data in this study are primary. Data was collected by using a questionnaire. The analytical method uses multiple linear regression models to test the hypothesis simultaneously using the F-test and partially using the t-test. The test results show an influence of School Culture, Professional Competence, and Organizational Commitment on teacher performance. The magnitude of the influence is shown by the coefficient of determination R2 (R square) = 19.9, meaning that School Culture, Professional Competence, and Organizational Commitment influence teacher performance by 19.9% ​​, and other factors determine the remaining 43.5%. The results of simple regression analysis show the equation Ŷ = 51.106+ 0.825X1 + 0.365X2+0.472X3. In conclusion, there is an influence of school culture, professional competence, and organizational commitment to teacher performance Keywords: School Culture, Professional Competence, and Organizational Commitment to Teacher Performance